Using a halogen lamp to calibrate an optical system for UV-VIS radiation detection - Yubero, Cristina; Garcia, M. Carmen; Calzada, M. Dolores (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
In the last few years plasmas have been used more and more in a great number of scientific and technological fields, and optical emission spectroscopy (OES) has been the most commonly used technique for their analysis. The usual optical system employed for plasma analysis is composed of a monochromator, a detector and an optical fiber, which must be calibrated to correct the different intensity response of each component in this system. For this calibration, the use of commercial halogen lamps is proposed as opposed to the commonly used ribbon lamp, involving lower economic cost.
Optica Applicata, Vol. 38, 2008, nr 2, s. 353-363
Keywords: optyka; calibration; optical system; patron sources; halogen lamp; plasma spectroscopy